Physiology and behaviour of juvenile snowshoe hares at the start of the 10-year cycle. (November 2019) - Lavergne, S.G.; Smith, K.; Kenney, A.; Krebs, C.J.; Palme, R.; Boonstra, R.
Abstract : Snowshoe hares, Lepus americanus, are the dominant prey species in the boreal forest and they undergo regular, predator-driven population cycles every 8–11 years. Previous research has found that hare stress physiology is highly sensitive to both within-year (seasonal/litter group) and across-year (cycle phase) variation in predation risk and that maternal–offspring stress profiles are tightly correlated. Thus, both pre- and postnatal environments may interact to shape offspring physiological phenotype. If changes in the function and reactivity of the maternal stress axis are associated with variation in offspring behaviours that increase survival during periods of high predation risk, then the maternal effects on offspring physiology seen previously could represent a mechanistic route of adaptive maternal programming. To examine the relationship between physiology and behaviour in snowshoe hares, we monitored free-ranging adult and juvenile stress hormone levels in the first and second litters of the breeding season and assessed open field exploratory behaviour in weaning-age and independent juveniles in the southwestern Yukon (Canada) during 2013–2015, when predator density was low but increasing. Thus, our study spanned the late low phase (2013) and the early increase phase (2014–2015) of the hare population cycle. We found that increased concentrations of faecal cortisol metabolites (FCMs) were associated with aspects of risk avoidance in weaning-age hares. Juveniles with higher stress hormone levels spent more time under cover and were less active during open field trials, highlighting a potential mechanistic route to allow individuals to sensitively cope with a changing environment. Although average FCM levels of breeding females and juveniles were not correlated with one another and litter-based differences in physiology and behaviour were not present during these low-risk phases of the cycle, the association between stress hormone levels and behaviour sets the stage for adaptive maternal effects on offspring behaviour and survival as the cycle progresses and predation risk intensifies. Highlights: Wild snowshoe hares are acutely sensitive to fluctuating predation risk. We measured population-level stress and juvenile open field exploratory behaviour. High faecal cortisol levels were associated with risk avoidance in juveniles. Pre- and postnatal environments influenced offspring physiological phenotype.